TG-ROC analysis of immunofluorescence assays in canine visceral leishmaniasis diagnosis - Silva, Rita Maria da; Laurenti, Márcia Dalastra; Gomes, Almério de Castro; Nogueira, Yeda Lopes (Revista de Saúde Pública, 2009)
OBJECTIVE: To analyze the accuracy of the diagnosis of two protocols of indirect immunofluorescence assays for canine visceral leishmaniasis. METHODS: Dogs from the seroepidemiological survey conducted in an endemic area of the cities of Araçatuba and Andradina, in Northwestern São Paulo state, in 2003, and in a non-endemic area of the metropolitan region of São Paulo, were used to assess two protocols of indirect immunofluorescence assay (IFA) for leishmaniasis: one using a Leishmania major heterologous antigen (IFA-BM) and another using a Leishmania chagasi homologous antigen (IFA-CH). Two-graph receiver operating characteristic (TG-ROC) analysis was used to estimate accuracy. TG-ROC analysis compared 1:20 dilution readings of the homologous antigen (IFA-CH), considered as reference test, with IFA-BM dilutions (heterologous antigen). RESULTS: The 1:20 dilution used in the IFA-CH test showed the best contingency coefficient (0.755) and the highest strength of association between the two variables studied (chi-square=124.3). Thus, it was considered the test reference dilution in comparisons with different IFA-BM test dilutions. The best IFA-BM results were obtained from 1:40 dilutions with the best contingency coefficient (0.680) and highest strength of association (chi-square=80.8). With the change in the cut-off point, recommended for the IFA-BM 1:40 dilution in this analysis, the specificity parameter value rose from 57.5% to 97.7%, even though the 1:80 dilution showed the best sensitivity estimate (80.2%), with the new cut-off point. CONCLUSIONS: TG-ROC analysis can provide important information about diagnostic tests, in addition to offering suggestions on cut-off points that can improve test sensitivity and specificity estimates and assessing these tests in terms of the best cost-benefit ratio.